Meminimalisir Waste pada Aktivitas Non-Value Added dengan Menggunakan Metode Value Stream Mapping di PT X - Nathanael Dicky (Jurnal Titra, 2022)
PT.X is a company that processes various types of wood in accordance with customer orders. The company has problems in the production process that quite often cause problems with delays in order fulfillment. The research was conducted by mapping the production process in woodworking and cutting which is the earliest process of the whole process. Mapping in woodworking and cutting process is done by using value stream mapping method, by designing current stae value stream mapping and future state value stream mapping. The research will focus on non-value added activities with the aim of suppressing non-value added contained in the woodworking and cutting processes. The results of data analysis showed that the cause of non-value added time is in the process of stick and shape grading. The proposal is designed based on a 5-whys analysis to find the root cause of the stick process and shape grading. In the future state value stream mapping shows that by implementing the proposal can improve the efficiency of production time and lead time. The percentage of production time efficiency between the current condition and the proposal is 4.83% while the lead time is 35.99%.